DESIGN CONCEPT FOR THE DEVELOPMENT OF NATURAL PLANT FIBER EXTRACTOR AS A RAW MATERIAL FOR NATURAL FIBER COMPOSITES - Azizi, M; Susilo, R. Dwi Pudji; Sebayang, Darwin; Fitri, Muhamad (Politeknik Negeri Sriwijaya, Indonesia, 2024)
The design concept is used for the development of natural plant fiber extractors as raw materials for making natural fiber composites. The extractor is a tool used to extract natural plant fibers which are expected to produce natural fibers as raw materials for making natural fiber composites. In the previous tool, there are still several shortcomings that can be redeveloped, both for the sake of the tool itself and in terms of the fiber produced. In this journal, it is focused on making design concepts before the development of the extractor tool, including identifying problems in previous tools, determining the functional structure, finding solutions to existing problems, determining development specifications on the tool and also evaluating from the technical and economic side. In the process of this design concept, There are several things that are highlighted in the previous tools to be developed, including the mobility of the tool, the quality and quantity of fiber produced, production time and safety aspects and also environmentally friendly. Thus, in the end, all of it will be narrowed down to the choice of specifications needed to support this with the consideration of the objective tree.